Experimental Set-up for vibration and impact analysis in robotics - Lima, Miguel F. M. (2019)
In this paper a laboratory apparatus is presented to study vibrations and phenomena. The experimental setup consists in real time acquisition and control system that acquires signals from internal and external robotic sensors. Several signals are acquired based on several experiments, both with vibrations and impacts caused by a flexible rod or a flexible beam, showing the capabilities of the system.